Uptake and translocation of polybrominated diphenyl ethers in the rhizosphere soil–crop–atmosphere system in e-waste dismantling areas in Taizhou, China. (October 2021) - Chen, Wenming; Liu, Chen; Wei, Baokai; Bao, Junsong; Wang, Ying; Hu, Jicheng; Jin, Jun; Zeng, Fangang
Abstract: Air, crop, and rhizosphere soil samples were collected from e-waste dismantling areas in Taizhou City (Zhejiang Province, China). The mean PBDEs (Polybrominated diphenyl ethers) concentrations in air in the Fengjiang and Binhai areas were 27.8 and 25.1 pg m −3, respectively (no significant difference, P > 0.05). The mean PBDE concentrations in rhizosphere soil from Fengjiang and Binhai were 9.19 × 10 4 and 1.34 × 10 3 pg g −1 dry weight, respectively (no significant difference, P > 0.05). The mean PBDE concentrations in the crop samples from Fengjiang and Binhai were 1.38 × 10 3 and 6.64 × 10 2 pg g −1 dry weight, respectively (no significant difference, P > 0.05). PBDEs with≥6 bromine atoms (BDEs-153, -154, −183, and −190) were not translocated from the crop roots to other tissues. PBDEs were taken up by crops selectively. The root epidermis effectively prevented PBDEs from entering edible crop parts and kept the PBDE concentrations in edible roots low. PBDEs with≤5 bromine atoms (BDEs-15, -28, −47, −66, −85, −99, and −100) were selectively enriched from the rhizosphere soil into crop roots, but PBDEs with more bromine substituents were not transferred from the rhizosphere soil to the crop roots. PBDEs with≥6 bromine atoms were selectively enriched from the atmosphere into crop leaves. Crop roots and leaves took up PBDEs with ortho bromine substituents more readily than PBDEs with meta bromine substituents because the octanol–water partition coefficients are lower for ortho-brominated than meta-brominated PBDEs. Highlights: PBDEs with≥6 bromine atoms were not translocated within crops. PBDEs with≤5 bromine atoms were selectively enriched from rhizosphere soil into crop roots. PBDEs with≥6 bromine atoms were selectively enriched from the atmosphere to crop leaves. Ortho -brominated PBDEs entered crops more readily than meta -brominated PBDEs.